Corporate governanace and corporate scandals - Mursalov, Elvin (2022)
In its most basic form, corporate governance is an approach to managing businesses with the intention of producing the greatest possible benefits for the shareholders and other stakeholders involved. This approach has become one of the most hotly debated topics in the world of business in recent years. In recent years, there has been a great deal of interest in the topic of corporate governance. This is largely attributable to the fact that good corporate governance clearly contributes to the overall economic well-being of both institutions and society. Furthermore, good corporate governance is a requirement that has become necessary as a result of globalization and the shifting nature of the competitive environment. This diploma thesis has been done on corporate scandals, which has been documented in the relevant literature. As a result of the advances that have taken place, it has begun to be addressed by international organizations, governments, firms, and many organizations, all of which are looking for the most effective form of corporate governance in order to avoid scandals. The aim of thesis is to investigate recent corporate scandals and find out reasons led to them. The main research question of the study is “What are the causes of corporate scandals and how they can be avoided?”. Aim and question of thesis is tried to be solved through case study of Parmalat case. This investigation focuses on the phenomena of corporate scandal, including its impact and the factors that contributed to its emergence in other countries during the past several years. In order to contribute to the identification of the processes that led to the scandal in some institutions, a real scandal examples were examined. In addition, other major scandals and foreign publications on corporate governance were scanned, and important findings from regulatory institutions were used.